2006
DOI: 10.1128/iai.74.3.1565-1572.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency ofChlamydia trachomatisMajor Outer Membrane Protein-Specific CD8+T Lymphocytes in Active Trachoma Is Associated with Current Ocular Infection

Abstract: Chlamydia-specific cytotoxic T lymphocytes are able to control model infections but may be implicated in disease pathogenesis. HLA-A2 peptide tetramers to Chlamydia trachomatis major outer membrane protein 258-266 (MOMP258-266) and MOMP260-268 were used to characterize HLA class I-restricted CD8 ؉ T cells in Gambian children aged 4 to 15 years with clinical signs of active trachoma and/or infection with C. trachomatis. The frequencies of circulating HLA-A2 tetramer binding cells (TBC) were determined in whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Conversely, we found that MOMP had no effect on the expression of CD40L in CD8 + T cells suggesting once more a selective effect of MOMP on T-helper-mediated immune responses. Our result contrast with previous findings showing that MOMP or MOMP-derived peptides significantly increase the proliferation of antigen-specific CD8 + T cells in vivo (Kim et al 1999;Rodriguez et al 2006;Holland et al 2006;Mahdi et al 2001) suggesting the participation of other antigen presenting cells and components of the immune response that may be absent in our in vitro setting and that could play a key role in the induction of CD8 + T cell responses in vivo.…”
Section: Discussioncontrasting
confidence: 86%
“…Conversely, we found that MOMP had no effect on the expression of CD40L in CD8 + T cells suggesting once more a selective effect of MOMP on T-helper-mediated immune responses. Our result contrast with previous findings showing that MOMP or MOMP-derived peptides significantly increase the proliferation of antigen-specific CD8 + T cells in vivo (Kim et al 1999;Rodriguez et al 2006;Holland et al 2006;Mahdi et al 2001) suggesting the participation of other antigen presenting cells and components of the immune response that may be absent in our in vitro setting and that could play a key role in the induction of CD8 + T cell responses in vivo.…”
Section: Discussioncontrasting
confidence: 86%
“…These findings were then applied to a clinical study of trachoma where the frequency of MOMP-specific CD8+ T lymphocytes in peripheral blood were sought. Frequency of these cells correlated with active ocular infection, but sample sizes were too small to relate to protection or disease outcome [74]. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, peptides derived from chlamydial proteins are known to be presented by MHC class I molecules (reviewed in reference 1) and Chlamydia-reactive CD8 ϩ T cells have been detected in patients (2,3). Despite the presence of antigen-specific T cells, infection with Chlamydia trachomatis can cause serious diseases in humans.…”
Section: A Ctivated Cytotoxic Cd8mentioning
confidence: 99%